ANALYTICAL THINKING SKILLS OF TEACHER CANDIDATE STUDENTS WITH APPLYING RESEARCH-BASED LEARNING (RBL) MODELS IN NATURAL SCIENCE: - Suyatman, Suyatman; Chusni, Muhammad Minan (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to analyze the analytical thinking skills of prospective teacher students in scientific learning of energy materials by applying a Research-Based Learning model (RBL). This study used a mixed method with a sequential explanatory design. The respondents selected through purposive sampling were 70 students, and 2 of them were for interview data. The research data was collected using a test instrument in the form of 10 essay questions and a non-test in the form of open interviews to students. The average pre-test score for the essay test was 45.71, the post-test score was 68.71, and the N-gain value was 42.37%. These results provide information about analytical thinking skills on energy concepts which are still in the moderate category, so alternative learning strategies are needed to improve the ability of prospective teachers in science learning. This research has recently developed five indicators of analytical thinking skills based on quantitative and qualitative studies on energy materials in science learning. Abstrak: Penelitian ini bertujuan untuk menganalisis keterampilan berpikir analitis mahasiswa calon guru dalam pembelajaran saintifik materi energi dengan menerapkan model pembelajaran berbasis penelitian (RBL). Penelitian ini menggunakan mixed method dengan desain sequential explanatory. Responden yang dipilih melalui purposive sampling sebanyak 70 siswa, dan 2 diantaranya untuk data wawancara.. Data penelitian dikumpulkan dengan menggunakan instrumen tes berupa 10 soal essay dan non-test berupa wawancara terbuka kepada siswa. Rata-rata nilai pretest tes esai adalah 45,71, nilai posttest 68,71, dan nilai N-gain 42,37%. Hasil tersebut memberikan informasi tentang keterampilan berpikir analitis pada konsep energi yang masih dalam kategori sedang, sehingga diperlukan alternatif strategi pembelajaran untuk meningkatkan kemampuan calon guru dalam pembelajaran sains. Penelitian ini memiliki kebaruan mengembangkan lima indikator kemampuan berpikir analitis berdasarkan kajian kuantitatif dan kualitatif pada materi energi dalam pembelajaran IPA.